Kemandirian Belajar Peserta Didik yang Tinggal dengan Orangtua Single Parent - Anugrah Oga Putra (Universitas PGRI SUMATERA BARAT, 2020)
ABSTRACT This research is motivated by the existence of students who live with single parents either order of words live with fathers or who live with mothers less independent in learning. The purpose of this study was to describe the learning independence of students living with single parent parents viewed from: 1) Confident in learning, 2) Able to work alone in learning, 3) Mastering expertise and learning skills, 4) Apprexcite learning time, 5) Responsible for learning. This research is a qualitative research. There are two key informants in this study, namely JMP and CTP as well as three additional informants consisting of the homeroom teacher, guidance and counseling teacher, subject teacher, and close friend. The instruments use in this study was observation and interview guidelines, data analysis techniques used are data reduction, data display and verification/inference. The result of the study revealed that the learning independence of students living with single parent parents was: 1) JMP and CTP are less confident in learning. 2) JMP and CTP are less capable of self-study. 3) JMP lacks expertise and learning skills, whereas CTP has mastered learning expertise and skills. 4) JMP and CTP do not appreciate the time spent studying. 5) JMP is less responsible for learning, whereas CTP is already responsible for learning. Key Word : Independence of Learning, Single Parent ABSTRAKPenelitian ini dilatarbelakangi adanya siswa kurang mandiri dalam belajar yang tinggal dengan orang tua tunggal baik tinggal bersama ayah maupun ibu. Tujuan penelitian ini adalah untuk mendeskripsikan kemandirian belajar siswa yang tinggal dengan orang tua tunggal dilihat dari: 1) Percaya diri dalam belajar, 2) Mampu bekerja sendiri dalam belajar, 3) Menguasai keahlian dan keterampilan belajar, 4) Menghargai waktu belajar, 5) Bertanggung jawab untuk belajar. Penelitian ini merupakan penelitian kualitatif. Ada dua informan kunci dalam penelitian ini yaitu JMP dan CTP serta tiga informan tambahan yang terdiri dari wali kelas, guru bimbingan dan konseling, guru mata pelajaran, dan teman dekat. Instrumen yang digunakan dalam penelitian ini adalah pedoman observasi dan wawancara, data dianalisis dengan reduksi data, display data dan verifikasi. Hasil penelitian mengungkapkan bahwa kemandirian belajar siswa yang tinggal dengan orang tua tunggal adalah: 1) JMP dan CTP kurang percaya diri dalam belajar. 2) JMP dan CTP kurang mampu belajar mandiri. 3) JMP kurang memiliki keahlian dan keterampilan belajar, sedangkan CTP telah menguasai keahlian dan keterampilan belajar. 4) JMP dan CTP tidak menghargai waktu yang dihabiskan untuk belajar. 5) JMP kurang bertanggung jawab untuk belajar, sedangkan CTP sudah bertanggung jawab untuk belajar. Kata Kunci : Kemandirian Belajar, Orangtua Tunggal